FORMATION OF HYDROPHOBIZED NUTRIA VELOUR - Anatolii Danylkovych; Nataliia Khliebnikova (Academic Scientific Journal of Chemistry, 2020)
The formation of hydrophobized nutria fur velour has been carried out using the optimized alkenmalein acrylsyntane composition. Based on the implementation of the synthesized experimental plan “composition-properties of velour” by the modified McLean-Anderson method, the optimization of filling and hydrophobizing composition has been performed by Harrington method. The optimized composition involves the use of, wt. %: alkenmalein polymer – 54.1, polyacrylic emulsion Melio Resin A-821 – 18.8, reagent based on 2-naphtholesulfonic acid and dioxins-phenylsulfone – 27.1. The developed technology of forming hydrophobized nutria velour has been tested at the experimental production of leather enterprise (Chinbar Private Joint Stock Company, Kyiv, Ukraine). Nutria fur velour obtained by the developed technology is characterized by a significant increase in water resistance in dynamic conditions. The advantage of this technology is the production of fur velour with a higher yield of 5.4–5.6 % compared to the semi-finished chromium-aluminum tanning. The optimized filling and hydrophobizing composition can be effectively used in the technologies of manufacturing sheepskin and leather materials with high water resistance. According to the complex of properties, the obtained hydrophobized nutria velour is suitable for the production of uncovered items of various purposes, which will be used in extreme conditions.